Role of FGF-18 in Bone Regeneration - Kavipriya Murugaiyan; Sivashanmugam Amirthalingam; Nathaniel Suk-Yeon Hwang; Rangasamy Jayakumar (Journal of Functional Biomaterials, 2023)
In tissue engineering, three key components are cells, biological/mechanical cues, and scaffolds. Biological cues are normally proteins such as growth factors and their derivatives, bioactive molecules, and the regulators of a gene. Numerous growth factors such as VEGF, FGF, and TGF-β are being studied and applied in different studies. The carriers used to release these growth factors also play an important role in their functioning. From the early part of the 1990s, more research has beenconductedon the role of fibroblast growth factors on the various physiological functions in our body. The fibroblast growth factor family contains 22 members. Fibroblast growth factors such as 2, 9, and 18 are mainly associated with the differentiation of osteoblasts and in bone regeneration. FGF-18 stimulates the PI3K/ERK pathway and smad1/5/8 pathway mediated via BMP-2 by blocking its antagonist, which is essential for bone formation. FGF-18 incorporated hydrogel and scaffolds had showed enhanced bone regeneration. This review highlights these functions and current trends using this growth factor and potential outcomes in the field of bone regeneration.